Analytical modelling and experimental assessment of metal pallets. Mechanical behaviour and durability performance under microbiological, chemical and environmental attacks - Enrico Zacchei; Miguel Esteves; Ana Azevedo; Saúl Martins; João Almeida; António Tadeu; Samuel Silva (Case Studies in Construction Materials, 2024)
Although pallets made of different materials are used to transport goods in large quantities worldwide, traditional codes provide design values not directly applicable to metal pallets. In this work, a mechanical model has been proposed by providing simplified analytic exact equations for these types of pallets. This model offers improvements over the current references, considering only the loadings and geometry. Under the described assumptions, this mechanical model could be adopted for pallets of different materials. Several experimental tests were carried out to assess the real mechanical behaviour of metal pallets made of aluminium and steel under specific loadings, and to estimate their performance under chemical, microbiological and environmental attacks compared to wood and plastic. The results have shown that metal pallets provide a good global performance.